Transparency: Informed Consent in Primary Care - Brody, Howard (The Hastings Center report, 1989)
Current legal standards of informed consent send the wrong message to physicians about their moral and legal expectations. A “transparency” model that sees consent as a conversation process can enhance good medical practice and patient autonomy without foreclosing appropriate judicial review.